2021
DOI: 10.3390/ijms222413190
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Conjugation with Octaarginine, a Cell-Penetrating Peptide on Antifungal Activity of Imidazoacridinone Derivative

Abstract: Acridine cell-penetrating peptide conjugates are an extremely important family of compounds in antitumor chemotherapy. These conjugates are not so widely analysed in antimicrobial therapy, although bioactive peptides could be used as nanocarriers to smuggle antimicrobial compounds. An octaarginine conjugate of an imidazoacridinone derivative (Compound 1-R8) synthetized by us exhibited high antifungal activity against reference and fluconazole-resistant clinical strains (MICs ≤ 4 μg mL−1). Our results clearly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 43 publications
(82 reference statements)
1
21
0
Order By: Relevance
“…For example, previous research showed that Candida TOPOII demonstrates less sensitivity for m-AMSA (Amsacrine; 4′-(9-Acridinylamino)methanesulfon-m-anisidide, acridine-compound) and etoposide than human enzyme while podophyllotoxins are inactive against mammalian enzyme but inhibit the activity of fungal TOPOII 13 . Also, our results obtained for antitumor imidazoacridinone C-1311 and triazoloacridinone C-1305 , whose molecular mechanism of action is related to hTOPOII poisoning 14 , 15 , indicated that the fungal enzyme is much less sensitive to both compounds than the human one 16 . Moreover, our preliminary studies showed that acridine/acridone derivatives may effectively inhibit yeast TOPOII (yTOPOII), which could be related to their antifungal activity 16 18 .…”
Section: Introductionmentioning
confidence: 73%
“…For example, previous research showed that Candida TOPOII demonstrates less sensitivity for m-AMSA (Amsacrine; 4′-(9-Acridinylamino)methanesulfon-m-anisidide, acridine-compound) and etoposide than human enzyme while podophyllotoxins are inactive against mammalian enzyme but inhibit the activity of fungal TOPOII 13 . Also, our results obtained for antitumor imidazoacridinone C-1311 and triazoloacridinone C-1305 , whose molecular mechanism of action is related to hTOPOII poisoning 14 , 15 , indicated that the fungal enzyme is much less sensitive to both compounds than the human one 16 . Moreover, our preliminary studies showed that acridine/acridone derivatives may effectively inhibit yeast TOPOII (yTOPOII), which could be related to their antifungal activity 16 18 .…”
Section: Introductionmentioning
confidence: 73%
“…Anticancer active conjugates of acridine can also be used as nanocarriers for antimicrobial compounds . Acridine and acridinone derivatives exhibit a wide spectrum of activity due to their effect on DNA damage, DNA repair and replication, inhibition of topoisomerase I and II, and induction of apoptosis. , Octaarginine imidazoacridinone derivative conjugate (5-((2-aminoethyl)­amino)-8-hydroxy-6H-imidazo­[4,5,1-de]­acridin-6-one) (Figure b, Table ) showed high antifungal activity against clinical reference and fluconazole-resistant strains ( C. albicans , C. glabrata , C. krusei , C. parapsiloris , S. cerevisiae MIC 90 0.25–4 μg/mL).…”
Section: Resultsmentioning
confidence: 99%
“…The tested conjugate changed the permeability of the fungal cell membrane and inhibited the activity of yeast topoisomerase II. No hemolytic activity was observed, and it showed low cytotoxicity against human embryonic renal cell carcinoma (HEK-293) and human liver (HEPG2) cell lines …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations